The Proof of Mass Decay - Gimsa, Andreas (International Journal of Scientific Research and Management (IJSRM), 2021)
It is high time that scientists recognise the general mass decay of all objects in the universe. Otherwise, the process of physical knowledge will remain severely limited. For the world is changeable and existing material structures, including the masses, must change with it. Change presupposes a flow of time, which in turn is influenced and caused by matter [1.].